Pengaruh Fasilitas Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Tehoru Kabupaten Maluku Tengah - Ambarwati Soetiksno; Jean R. Asthenu; Hesti Karim (Jurnal Administrasi Terapan, 2024)
An initial survey at the Tehoru District Office, Central Maluku Regency showed that there were indications of problems with work facilities and employee performance. This research aims to determine and analyze the influence of work facilities on employee performance in the Tehoru District Office, Central Maluku Regency. The analytical method used in this research is quantitative analysis and simple linear regression analysis. Quantitative analysis shows that work facilities at the Tehoru District Office have an average value of 3,40 which is interpreted as quite good, while employee performance has an average value of 3,54 which is interpreted as quite good. The results of the regression analysis show that work facilities have a positive effect on employee performance at the Tehoru District Office, Central Maluku Regency. Based on these results, it can be concluded that the better the work facilities, the better the employee performance. To improve it, the Tehoru District Office must stive to improve work facilities used by employees so that employees can work effectively. Keywords: Work Facilities, Employee Performance